Legal responsibility of foreign doctors who commit medical malpractice in Indonesia - Marune, Abraham Ethan Martupa Sahat (Institute of Computer Science (IOCS), 2024)
This research investigates the legal liability of foreign doctors in cases of malpractice and illegal medical practices in Indonesia. It explores the legal framework governing such practices and the protection available to victims. Despite existing laws such as Law Number 8 of 1999 concerning Consumer Protection and Law Number 29 concerning Medical Practice, they fail to adequately safeguard patients, particularly in cases involving foreign doctors. Although legislation mandates health as a human right and outlines legal protection for victims, enforcement is lacking. There's a notable absence of specific regulations governing the supervision of foreign doctors practicing in Indonesia. While various laws touch on aspects of supervision and regulation, such as Law Number 13 of 2003 concerning Employment and Law Number 6 of 2011 concerning Immigration, they lack specificity. The research recommends revising and enhancing legal regulations to address these gaps, particularly focusing on regulations pertaining to foreign doctors' practices and patient protection. This includes advocating for specialized regulations tailored to address malpractice committed by foreign doctors and ensuring their enforcement to uphold patient safety and rights.